Nanoscale science and technology education: primary school students' preconceptions of the lotus effect and the concept of size - Peikos, George; Spyrtou, Anna; Pnevmatikos, Dimitris; Papadopoulou, Penelope (Research in science & technological education, 2023)
It is stated that it is necessary that students develop their nanoliteracy in order to come up with everyday issues arising from Nanoscale Science and Technology (NST) applications, taking informed decisions and estimating the potential risks and benefits. Even though the inclusion of NST in compulsory education is supported by many researchers, the research on students' preconceptions of NST concepts and phenomena is in its infancy. We aim to identify students' preconceptions of (a) the conceptualization of size in the context of NST and (b) the explanation of the lotus effect (superhydrophobic materials). The participants of our research are 250: 5 th and 6 th grade primary school students in Greece. The data collection tool is a written questionnaire. Regarding the coding, both the inductive and deductive qualitative process is followed. Concerning the concept of size, approximately half of the students are aware of non-visible objects. However, their classification of objects based on size is naive and based on vague criteria e.g. 'Large, Medium, Small objects'. For the lotus effect we identify three categories consisting of thirteen subcategories that reflect students' ideas about their macroscopic view of the lotus effect explanation. Students see the explanation of the lotus effect as a Direct process (explanations based on an identifiable causal agent). We argue that we could support them shift their explanations to the Emergent process (explanations based on non-identifiable causal agents) using appropriate tasks. Concerning the concept of size, students are aware of two main categories: the visible and non-visible objects. We could help them create the macro-, micro- and nanoworld categories based on qualitative criteria.